REPRESENTATION OF SOCIAL VALUE AND SEXUAL HARASSMENT DUE TO MALE DOMINATION IN MOVIE WOMEN TALKING BY SARAH POLLEY - Zahrah Hana Afifah; Danang Dwi Harmoko; Suwarsito Suwarsito (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This research aims to determine various social values and sexual harassment due to male dominance in the film Women Talking by Sarah Polley. This research was conducted using a qualitative descriptive method. The data in this research were obtained from dialogue in the film Women Talking by Sarah Polley which was analyzed based on social value theory and sexual harassment theory from various sources. Thus, the results of this research produce 4 types of social values, including truth value, religious and internalised value, democratic value, and dominant value. Meanwhile, only 1 type of sexual harassment was found, namely physical sexual harassment. And there are 2 implications of sexual harassment, including emotional or psychological problems and physical problems. This research uses the relationship between the dominance of men who have power over women. Therefore, this research is important to find out the message or meaning that the researcher wants to convey in her work. Keywords: Male domination, sexual harassment, social value